2007
DOI: 10.1145/1297105.1297046
|View full text |Cite
|
Sign up to set email alerts
|

The causes of bloat, the limits of health

Abstract: Applications often have large runtime memory requirements. In some cases, large memory footprint helps accomplish an important functional, performance, or engineering requirement. A large cache, for example, may ameliorate a pernicious performance problem. In general, however, finding a good balance between memory consumption and other requirements is quite challenging. To do so, the development team must distinguish effective from excessive use of memory.We introduce health signatures to enable these distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 17 publications
1
40
1
Order By: Relevance
“…High-level languages abstract memory management and object layout to improve programmer productivity, usability, and security, but abstraction usually costs. Mitchell and Sevitsky study bloat, spurious memory consumption caused by careless programming [22]. A shocking fraction of the Java heap is bloat, motivating the need for space savings.…”
Section: Read and Write Barriersmentioning
confidence: 99%
“…High-level languages abstract memory management and object layout to improve programmer productivity, usability, and security, but abstraction usually costs. Mitchell and Sevitsky study bloat, spurious memory consumption caused by careless programming [22]. A shocking fraction of the Java heap is bloat, motivating the need for space savings.…”
Section: Read and Write Barriersmentioning
confidence: 99%
“…Modeling and characterization. Mitchell and Sevitsky categorize fields by the role they play in an object (header, pointer, null, primitive), and categorize objects by the role they play in a data structure (head, array, entry, contained) [18]. These measures together with scaling formulas predict the heap data reductions of manual program changes.…”
Section: Related Workmentioning
confidence: 99%
“…Researchers have characterized Java memory usage patterns [5,11,18], but do not study memory savings opportunities. A number of researchers propose and measure specific compression approaches [2,4,7,8,9,14,17,19,22,23,30].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore not surprising that recent studies [22] have shown that in some production systems, the utilization of collections might be as low as 10%, that is, 90% of the space consumed by collections in the program is overhead.…”
Section: Introductionmentioning
confidence: 99%
“…PLDI'09, June 15-20, 2009 Existing profilers ignore collection semantics and memory layout, and aggregate information based on types. Offline approaches using heap-snapshots (e.g., [21,22]) lack information about access patterns, and cannot correlate heap information back to the relevant program site.…”
Section: Introductionmentioning
confidence: 99%